Instagram sebagai media komunikasi Perpustakaan UIN SAIZU - Ningrum, Ayuk Kusuma (Daluang: Journal of Library and Information Science, 2022)
Introduction. During the pandemic, the Library of UIN Prof. K.H. Saifuddin Zuhri Purwokerto (UIN SAIZU) run into many service changes. Libraries must think about how to communicate to users regarding the latest collections, announcements of service changes, socialization of library activities, documentation of library activities, and social-cultural activities. This study examines Instagram as a medium of communication to users.Methodology. The research method uses qualitative methods and data collection techniques using interviews and observations.Results and discussion. The results show that libraries have used Instagram to communicate library-related matters by using various features available on Instagram. Libraries also manage accounts by creating exciting content to increase engagement rate.Conclusion. Using social media as a communication medium can be utilized by libraries, both university libraries and other types of libraries. The UIN SAIZU library can disseminate information quickly, efficiently, and interestingly. It has a broad reach. Some features allow getting feedback from the audience in the form of comments, likes, and messages.